PENINDASAN TERHADAP WANITA YANG DIGAMBARKAN DALAM NOVEL THE GIRL ON THE TRAIN OLEH PAULA HAWKINS - POSUMAH, WILLY REYNALD (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTThis skripsi is entitled Penindasan terhadap Wanita yang digambarkan dalam novel The Girl on the Train oleh Paula Hawkins. The objectives of this research are to identify, analyze and describe the oppression as well as to analyze the effects of the oppression portrayed through characters in The Girl on the Train by Paula Hawkins.The writer based to his research on the theory of Iris Young in Oppression, Privilege, and Resistance. According to Young, there are five faces of oppression that consists of; exploitation, marginalization, powerlessness, cultural imperialism, and violence.In conducting this study, the writer uses intrinsic and extrinsic approaches, and also this skripsi is data qualitative analysis in which the process consists of describing, analyzing, and interpreting process. Intrinsic element is used to analyze and identify the characters, and the extrinsic element is used to analyze and describe the types of oppression that oppressed the characters as well as the women, the victim through the novel, and the writer also will classify the effects of the oppression. These approaches are applied in order to get the appropriate analysis and to answer the problems. The data are taken from the novel The Girl on the Train by Paula Hawkins whereas the result of this research are the description of event which to know the characters, the women that get oppressed by the subjugation by classifying the five faces of oppression that consists of; exploitation, marginalization, powerlessness, cultural imperialism, and violence as well as the effects among the characters physically and psychologically.Keywords: oppression, oppression on women.